ISLAMIC UNITY: WHY IS THE UMMAH NOT UNITED AND HOW TO UNITED IT? - Ahmad Munirul Hakim (Journal of Islamic and Interdisciplinary Research, 2025)
This study aims to examine in depth the issue of "Islamic Unity: Why Are the Ummah Not United and How to Unite Them?" through a library research approach by examining classical and contemporary literature related to socio-religious dynamics in Islam. The disunity of the ummah often stems from differences in schools of thought, political interests, group fanaticism, and a lack of understanding of the values of tolerance and Islamic brotherhood taught by the Qur'an and the Sunnah. This study analyzes historical factors that have influenced the fragmentation of the ummah since the time of the Khulafaur Rasyidin to the modern era, including the influence of colonialism and globalization in shaping the social structure of the Muslim community. This study also identifies the role of education, da'wah, and moderate religious literacy as strategic paths to building unity. Efforts for inter-group reconciliation can be achieved through constructive dialogue, strengthening the principle of wasathiyah, and revitalizing the teachings of Islamic brotherhood. The results of the study indicate that unity is not only a theological issue but also a sociological and political one that requires collaboration between ulama, government, and society. Taking into account the value of rahmatan lil 'alamin (mercy for the universe), this study concludes that communal synergy will be more easily achieved through an inclusive approach, effective communication, and strengthening a shared vision. These findings are expected to provide theoretical contributions to the development of the discourse on Islamic unity as well as practical solutions for implementation in various contexts of communal life.